Kinetics and Mechanism of Oxidation of L-Cysteine by Bis-3-di-2-pyridylketone-2-thiophenylhydrazone-iron(III) Complex in Acidic Medium - Ismail Warad; Mohammed Al-Nuri; Maher Abu Eid; Zeid Al-Othman; Saud Al-Resayes; Nizam Diab (E-Journal of Chemistry)
The kinetics of oxidation of L-cysteine by 3-di-2-pyridylketone-2-thiophenylhydrazone-iron(III), [Fe(DPKTH)2] 3+ complex in acidic medium was studied spectrophotometrically at 36 °C temperature. The molar ratios of DPKTH to iron(III) and iron(II) individually, were found to be [2:1] [DPKTH : iron(III)/(II)]. The reaction was stroked to be first-order with respect to iron(III) and L-cysteine, second-order with respected to DPKTH ligand and reversed second-order with respected to hydrogen ion concentration. Added salts did not affect the rate and no free radical was detected when radical detector was placed in the reaction mixture. Ethanol solvent ratio was found to effect both the initial rate and the maximum absorbance (λmax) of [Fe(DPKTH) 2]2+ complex. The initial rate rose when the temperature was increased which empowered to calculate the activation parameters. A suitable reaction mechanism was proposed.